ANALISIS IMPLEMENTASI KEBIJAKAN SISTEM ELECTRONIC FILING SEBAGAI UPAYA MENINGKATKAN KEPATUHAN WAJIB PAJAK DALAM PENYAMPAIAN SURAT PEMBERITAHUAN TAHUNAN KEPADA KPPPRATAMA TANGGERANG BARAT TAHUN 2013, 2014, DAN 2015 - Atong Soekirman; Hasan Rachmany; Veronica Very Happy (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
The Analysis of Implementation Policy’sElectronic Filing System for Compliance of tax payer improvement on communicating SPT to KPP Pratama’s West Tangerang 2013, 2014, & 2015. The purpose of this research is to know the implementation’s policies of e- Filing for compliance of tax payer improvement on KPP Pratama’s West Tangerang 2013, 2014, & 2015. Theory in this research refers to George Edward lII’s theory, there are four factors that influence of implementation’s policy such as : communication, resources, disposition / nature, and a bureaucracy’s structure. This research using inductive analysis’ method. Datas obtained by depth interviews, direct observation and documentation research. The subject of this research is tax officials, tax payer, and academics with informants determination using purposive sampling’s technique. This research through validity test with four test criteria credibility, transferability, dependability, and confirmability. Based on the analysis, it showed that: there is an increasing amount of their annual tax return submitted by e-Filingfrom 2013 amounted to 18,397 and in 2014 amounted to 25,552 and in 2015 amounted to 54, 693, it proves that  the implementation of policies on e-Filing going well and can be received by the taxpayer.